Comparing Special Education : Origins to Contemporary Paradoxes - Richardson, John G. (Stanford University Press, 2011)
In contemporary conflicts about educational standards and accountability, special education plays a key role as it draws the boundaries between exclusion and inclusion. This book unites in-depth comparative and historical studies with analyses of global trends.